Ending the Microfinance Crisis in Morocco : Acting Early, Acting Right - International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
In the fall of 2008, the Moroccan microfinance sector underwent what in economics is referred to as a Minsky moment, the sudden realization that the market has overshot and that the good times are coming to an end. In this particular case, the Minsky moment was a specific event – the private circulation of an IFC study that found extensive problems with the portfolios of the country’s four largest Microfinance Institutions (MFIs), and one in particular – Zakoura. This study picks up from Morocco’s Minsky moment. The MFIs at the time were beginning to see unequivocal signs that the market was shifting. The lead-up to this moment has been well documented: the reckless pursuit of growth, fed by an equally reckless influx of funding, both foreign and domestic, the high rate of multiple lending, poor lending standards and equally poor back-office and management information systems (MIS), and poor governance – all have been noted as causes of the crisis. While this study is meant to cover the full Moroccan microfinance sector, due to constraints of time and availability of data, its primary focus is on the three largest MFIs in Morocco. This report is organized into three key sections: 1) a review of the main drivers and factors evident during the course of the Moroccan microfinance crisis (2008-2011); 2) an examination of the key responses taken by the MFIs during the course of the crisis; and 3) a review of government actions and other market-level changes that affected the nature and trajectory of the crisis. The authors close with a look at the future prospects for microfinance in Morocco.